Microbial Transglutaminase Improves ex vivo Adhesion of Gelatin Methacryloyl Hydrogels to Human Cartilage - Trengove, Anna; Duchi, Serena; Onofrillo, Carmine; O'Connell, Cathal D.; Di Bella, Claudia; O'Connor, Andrea J. (Frontiers in Medical Technology, 2021)
Current surgical techniques to treat articular cartilage defects fail to produce a satisfactory long-term repair of the tissue. Regenerative approaches show promise in their ability to generate hyaline cartilage using biomaterials in combination with stem cells. However, the difficulty of seamlessly integrating the newly generated cartilage with the surrounding tissue remains a likely cause of long-term failure. To begin to address this integration issue, our strategy exploits a biological enzyme (microbial transglutaminase) to effect bioadhesion of a gelatin methacryloyl implant to host tissue. Mechanical characterization of the bioadhesive material shows that enzymatic crosslinking is compatible with photocrosslinking, allowing for a dual-crosslinked system with improved mechanical properties, and a slower degradation rate. Biocompatibility is illustrated with a 3D study of the metabolic activity of encapsulated human adipose derived stem cells. Furthermore, enzymatic crosslinking induced by transglutaminase is not prevented by the presence of cells, as measured by the bulk modulus of the material. Adhesion to human cartilage is demonstrated ex vivo with a significant increase in adhesive strength (5.82 ± 1.4 kPa as compared to 2.87 ± 0.9 kPa, p<0.01) due to the addition of transglutaminase. For the first time, we have characterized a bioadhesive material composed of microbial transglutaminase and GelMA that can encapsulate cells, be photocrosslinked, and bond to host cartilage, taking a step towards the integration of regenerative implants.